Tanggapan Siswa Terhadap pembiasaan Muhasabah Hubungannya Dengan Motivasi Belajar Mereka Pada Mata Pelajaran PAI - Azmi Nur Izzah; Qiqi Yuliati Zakiyah; Cecep Anwar (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this research is to find out how far the relationship between students' responses to the habit of muhasabah in PAI subjects is. The method is a correlational method with a quantitative approach. Respondents in this study amounted to 44 students of class VIII at SMPN 3 Bandung. This research approach is a quantitative approach using the correlation method. Respondents are 44 students of class VIII SMPN 3 Bandung, data collection techniques: Questionnaires, interviews, observations, and document studies. Data analysis was carried out with a logical approach for qualitative data and a statistical approach for quantitative data. Data collection techniques in the form of questionnaires, interviews, observations, and document studies. Based on the results of data analysis, conclusions were obtained: 1) The reality of student responses to muhasabah habituation (Variable X) was included in the positive category with an average value of 4.48 which was in the interval 3.51-4.50. 2) The reality of student learning motivation in PAI subjects (Variable Y) is included in the high category with a score of 4.28 in the interval 3.51-4.50. 3) The relationship between students responses to the habit of muhasabah with their learning motivation is positive and significant. Shown by the results of the correlation significance test obtained, namely: t_count 3.99> t_table 2.02. The correlation coefficient value is 0.52. The coefficient of determination reaches 27%, which means that there are 73% of other factors that influence their learning motivation in Islamic Religious Education subjects.